Role of IFN-γ and LPS on neuron/glial co-cultures infected by Neospora caninum - De Jesus, Erica Etelvina Viana; Santos, Alex Barbosa Dos; Ribeiro, Catia Suse Oliveira; Pinheiro, Alexandre Moraes; Freire, Songeli Menezes; El-Bachá, Ramon Santos; Costa, Silvia Lima; de Fatima Dias Costa, Maria (Frontiers in Cellular Neuroscience, 2014)
Neospora caninum causes cattle abortion and neurological symptoms in dogs. Although infection is usually asymptomatic, classical neurological symptoms of neosporosis may be associated with encephalitis. This parasite can grow in brain endothelial cells without markedly damages, but it can modulate the cellular environment to promote its survival in the brain. In previous studies, we described that IFN-γ decreased the parasite proliferation and down regulated nitric oxide (NO) production in astrocyte/microglia cultures. However, it remains unclear how glial cells respond to N. caninum in the presence of neurons. Therefore, we evaluated the effect of 300 IU/mL IFN-γ or 1.0 mg/mL of LPS on infected rat neuron/glial co-cultures. After 72 h of infection, LPS did not affect the mitochondrial dehydrogenase activity. However, IFN-γ decreased this parameter by 15.5 and 12.0% in uninfected and infected cells, respectively. The number of tachyzoites decreased 54.1 and 44.3% in cells stimulated with IFN-γ and LPS, respectively. Infection or LPS treatment did not change NO production. On the other hand, IFN-γ induced increased nitrite release in 55.7%, but the infection reverted this induction. IL-10 levels increased only in infected cultures (treated or not), meanwhile PGE2 release was improved in IFN-γ/infected or LPS/infected cells. Although IFN-γ significantly reduced the neurite length in uninfected cultures (42.64%; p < 0.001), this inflammatory cytokine reverted the impairment of neurite outgrowth induced by the infection (81.39%). The results suggest a neuroprotective potential response of glia to N. caninum infection under IFN-γ stimulus. This observation contributes to understand the immune mediated mechanisms of neosporosis in central nervous system (CNS).